PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA MAQASHID SYARIAH PADA BANK SYARIAH: PERAN MODERASI INTELLECTUAL CAPITAL - Nadia Khatun Zahra (2023)
This study aims to determine and analyze the effect of Good Corporate Governance (GCG) using the GCG mechanism, namely independen commissioners, DPS and audit committees on the performance of maqashid sharia and this study aims to determine the role of IC in moderating the effect of GCG on the performance of maqashid sharia with Islamic banking in Indonesia and Malaysia during the 2018-2020 period. The samples used by the researchers were 10 Islamic banks in Indonesia and 13 Islamic banks in Malaysia. In this study using secondary data sourced from the annual report and financial statements with a quantitative method. This study used the fixed effect model with panel data regression, data processing was carried out using STATA software version 13. Based on the test results, it was found that 2 GCG mechanisms, namely the sharia supervisory board and the audit committee, had a significant positive influence on the performance of maqashid sharia. The independent commissioner's GCG mechanism has no influence on the performance of maqashid sharia. As for intellectual capital, it cannot moderate the effect of GCG on the performance of maqashid sharia.